Study of Mappings and Metric Spaces in Fixed Point Theory: A Review - Rani, Asha; Bharti, (Communications in Mathematics and Applications, 2024)
Fixed point theory is a rich, fascinating, and intriguing subject of mathematics. Though it is a completely established field of research, but very fresh. It has been a hot topic of research since its inception. In this work, we present an overview of the major branches of fixed-point theory along with the key results. The focus of this article is to investigate different types of mappings and their variants. Furthermore, a survey of several extensions of metric space has also been carried out.
Keywords: Fixed points; Mappings; Metric spaces